On a subclass of analytic functions for operator on a Hilbert space - JOSHI, Sayali; JOSHI, Santosh B.; MOHAPATRA, Ram (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
In this paper we introduce and study a subclass of analytic functions for operators on a Hilbert space in the open unit disk U = fz 2 C : jzj < 1g. We have established coecient estimates, distortion theorem for this subclass, and also an application to operators based on fractional calculus for this class is investigated. Mathematics Subject Classification (2010): 30C45.